Study on Cracking Resistance of Basalt Fiber-Reinforced Microbond Asphalt Macadam - Xin Yan; Ronghua Ying; Jian Jin; Yuntai Zhang (Advances in Civil Engineering)
The aim of the present study was to explore the effect of basalt fibers on the cracking resistance of microbond asphalt macadam and reduce the occurrence of cracks in asphalt pavements with semirigid base. To this end, compressive resilient modulus tests, rutting tests, and semicircular bending tests were conducted on microbond asphalt macadam with different fiber contents, and the change trends of the compressive resilient modulus, dynamic stability, and flexibility index (FI) with fiber content were revealed. According to the results of this study, the addition of basalt fibers affected the compressive resilient modulus, dynamic stability, and FI of microbond asphalt macadam significantly. With the increase of fiber content, the compressive resilient modulus, dynamic stability, and FI presented a uniform trend of increasing first and decreasing afterwards. When the fiber content was 0.4%, various indices reached their maximum values, suggesting that the cracking resistance of the basalt fiber-reinforced microbond asphalt macadam was optimal under this content. This study is of great significance for the application and promotion of basalt fiber-reinforced microbond asphalt macadam.